2021
DOI: 10.3390/cancers13030568
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Cohort Study on 194 Supraglottic Cancer Patients: Implications for Laser Surgery and Adjuvant Treatment

Abstract: Supraglottic laryngeal cancer is characterized by poor prognosis. In contrast, excellent outcomes have been published in early-stage supraglottic cancers after laser surgery in single-institutional series in centers of excellence. Are these results reproducible in the normal clinical practice of less specialized facilities? As part of an observational cohort study, the outcomes of 194 supraglottic cancer patients were assessed after treatment by larynx-preserving surgery (transoral laser microsurgery [TLM] or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The main determinant of the radiation dose to the surgical tumor bed is represented by the pathologic margin. Notwithstanding the aim of surgery to achieve a microscopically radical resection, positive margins could occur in up to one-third of patients treated with CS for SG cancers [ 9 ]. Radiation oncologists recommended a dose of 62–66 Gy in case of positive margins for the majority of head and neck cancers, but the optimal dose to be administered to the remnant larynx in case of close/positive margins after a CS approach has not been standardized yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main determinant of the radiation dose to the surgical tumor bed is represented by the pathologic margin. Notwithstanding the aim of surgery to achieve a microscopically radical resection, positive margins could occur in up to one-third of patients treated with CS for SG cancers [ 9 ]. Radiation oncologists recommended a dose of 62–66 Gy in case of positive margins for the majority of head and neck cancers, but the optimal dose to be administered to the remnant larynx in case of close/positive margins after a CS approach has not been standardized yet.…”
Section: Discussionmentioning
confidence: 99%
“…While the outcomes are similar, the combination of CS and postoperative radiotherapy (PORT) can be burdened by a significant rate of relevant long-term side effects, especially when compared to the non-surgical strategy [ 6 , 7 , 8 ]. In particular, the treatment of the supraglottic (SG) region is associated with a higher rate of dysphagia and respiratory dysfunction, due to the crucial role of this area in the swallowing and breathing processes [ 9 ]. Consistently, up to one-third of patients treated with PORT following SG laryngectomy may require enteral nutrition and/or permanent tracheostomy, or experience chondronecrosis [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study was approved by the ethics committee of the Medical University of Heidelberg (Ethics Commission S-141/2008 Medical Faculty). As reported previously [ 21 , 22 , 23 ], all index laryngeal cancer patients were recruited from the five academic tertiary referral centers in the Rhein-Neckar-Odenwald region in southwest Germany between 5 January 1998 and 31 December 2004. Patients in this study either participated in a previous prospective case-control study between 1998 and 2000 or were identified retrospectively through patient records (2001–2004).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, functional outcomes of patients treated with this combined approach (surgery and PORT) may not be fully satisfactory. In particular, treatment of the supraglottic (SG) region is burdened by a higher rate of dysphagia and respiratory dysfunction, due to the crucial role of this area in swallowing and breathing 11 . Consistently, up to one-third of patients treated with PORT following conservative surgery may require enteral nutrition and/or permanent tracheostomy, or experience chondronecrosis [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%